2008
DOI: 10.1021/pr800562j
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of HepaRG Cells: A Novel Cell Line That Supports Hepatitis B Virus Infection

Abstract: The first proteomic characterization of the HepaRG cell line, the only cell line that is susceptible to hepatitis B virus (HBV) infection and supports a complete virus life cycle, is reported. Differential analysis of naive and HBV-infected HepaRG cells by two-dimensional gel electrophoresis revealed 19 differentially regulated features, 7 increasing and 12 decreasing with HBV infection. The proteins identified in these features were involved in various cellular pathways including apoptosis, DNA/RNA processing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 41 publications
4
19
0
Order By: Relevance
“…Basic markers for diagnosis of HBV infection include the presence of hepatitis B surface antigens (HBsAgs) and hepatitis B envelope antigens in acute or chronically infected hepatocytes [4,5]. Several physiological and biochemical methods have been developed to monitor HBV infection [6,7,8,9]. In addition, Abe et al reported quantitative analysis of HBV using DNA Polymerase chain reaction (PCR) assay [10].…”
Section: Introductionmentioning
confidence: 99%
“…Basic markers for diagnosis of HBV infection include the presence of hepatitis B surface antigens (HBsAgs) and hepatitis B envelope antigens in acute or chronically infected hepatocytes [4,5]. Several physiological and biochemical methods have been developed to monitor HBV infection [6,7,8,9]. In addition, Abe et al reported quantitative analysis of HBV using DNA Polymerase chain reaction (PCR) assay [10].…”
Section: Introductionmentioning
confidence: 99%
“…A previous proteomics study using HBV-uninfected and HBV-infected HepaRG cells identified 19 differentially-regulated proteins [12]. However, additional proteomic studies, more focused on plasma membrane proteins, (the first recognition partners during cell-virus interaction), are needed.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the complete life cycle of HBV infection—despite the usefulness of available human liver cell lines—there is clearly a strong need for appropriate in vitro infection systems, allowing for exogenous HBV infection [7]. HBV replication can be initiated by genomic DNA transfection into HepG2, Huh7, HepAD38, or primary hepatocytes [8]. However, until recent years, exogenous HBV infection has only been successfully achieved using primary human hepatocytes [9], [10].…”
Section: Introductionmentioning
confidence: 99%